PENGARUH TINGKAT PENCAHAYAAN TERHADAP VISUS HASIL PEMERIKSAAN REFRAKSI SUBJEKTIF DI DALAM RUANGAN - Muhammad Akbar Firmansyah; Wahyu Budiana; Nisa Zakiati Umami (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
This study aims to determine the difference in the level of illumination on the results of subjective refraction examinations and the condition of the patient when performing subjective refraction examinations at different lighting levels. The research method used is qualitative with a descriptive observational, by examining subjective refraction at bright (506 lx) and dim (120 lx) lighting levels. The sample of this study used the saturated sampling technique, the occupants of the boarding house by collecting data through observation, interviews, and documentation. The results of the study, it can be found that there are differences in the results of subjective refraction examinations. The differences obtained are based on the correction result, the initial vision sine correction, the final visual acuity cum correction, and the condition of the patient.